Optimisation the removal of Fe (II) ions from wastewater using clay- alginate composite beads - Antar, Antar Ahmed; Alsofiany, Asem Abdulqawi; Harun, Mohd Yusof (Tamkang University, 2022)
The increase in anthropogenic and agricultural activities has resulted in a significant discharge of heavy metalpolluted water into the environment. The removal of heavy metals from polluted water through the use of sustainable, low-cost, and biodegradable sorbents with high efficiency has become a research priority. The novel aspect of this work is the optimisation study of Fe (II) adsorption from wastewater by Clay-alginate composite beads. The synergistic combination of these adsorbents yields a composite of clay-biomass adsorbents with superior adsorption properties and high binding sites. The optimisation experiment was designed using the Box-Behnken method. In 46 experimental runs, five factors were investigated: initial pH (2-12), initial Fe (II) concentration (200-1000mg/l), stirring speed (0-250 rpm), adsorbent dosage (0.1-0.5 gm), and contact time (30-180 min). According to the ANOVA analysis, all factors are significant and have an impact on the removal efficiency. The optimum conditions for the selected factors are 10.23, 209mg/l, 65.34rpm, 0.107gm, and 128.6min for the initial pH, initial Fe (II) concentration, stirring speed, adsorbent dosage, and contact time, respectively. At these optimum conditions, removal efficiency could reach 52.9%. The findings of this study would be useful to researchers and those interested in wastewater treatment processes, particularly those involving the removal of heavy metals and hazardous waste.